2013
DOI: 10.1097/dcr.0b013e3182821e58
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Article

Abstract: Combined endolaparoscopic surgery appears to be a safe and effective alternative to colectomy in all parts of the colon in patients who have benign polyps not removable with colonoscopy alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…The literature showed that resected polyp size can range from 1.0 cm to 7.0 cm [11, 12]. In our experience the mean polyp size was 27.8 mm, with the largest reaching 5.0 cm in diameter, but polyp location was a more influential factor for LACP.…”
Section: Discussionmentioning
confidence: 47%
“…The literature showed that resected polyp size can range from 1.0 cm to 7.0 cm [11, 12]. In our experience the mean polyp size was 27.8 mm, with the largest reaching 5.0 cm in diameter, but polyp location was a more influential factor for LACP.…”
Section: Discussionmentioning
confidence: 47%
“…Franklin and Portillo [11] reported a postoperative complication rate of 9%, with no major complications and most of the reported complications were seroma, atelectasis, and ileus. Lee et al [12] reported a complication rate of 4.2%, and most of the complications were wound hematoma or urinary retention. Crawford et al [2] and Lee et al [12] reported rates of 10% and 9.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [12] reported a complication rate of 4.2%, and most of the complications were wound hematoma or urinary retention. Crawford et al [2] and Lee et al [12] reported rates of 10% and 9.2%, respectively. Both intraoperative and postoperative complications occurred in their CELS studies; additionally, they reported that the majority of complications were minor, and no complications resulted in long-term sequelae or the need for reoperation.…”
Section: Discussionmentioning
confidence: 99%
“…In approval of safety and efficacy of this technique, larger studies have been published by some other authors worldwide (8)(9)(10)(11). Moreover, Winter et .al published a study in 2007 that 38 patients with colon polyps underwent a laparoscopy assisted and laparoscopy monitored colonoscopic resection and in five cases, histopathologic diagnosis showed a malignancy necessitating colonic surgery.…”
Section: Indicationmentioning
confidence: 99%
“…In conclusion, combined endo-laparoscopic surgery (CELS) is developed for endoscopic colon polyps resection (5)(6)(7)(8)(9)(10)(11).…”
Section: Indicationmentioning
confidence: 99%